Percentage Of Body Fat Related With Functional Capacity In Young Adults - Delia Ainnaya; Mustika Anggiane Putri (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Introduction. The percentage of body fat is a component of body composition in addition to bone mass, muscle mass, and body water content related to obesity. Diseases caused by an increase in body fat will have an impact on decreasing the body's functional capacity, disability, and death. Maximum Oxygen Volume (VO2 max) refers to the maximum amount of oxygen that humans can use during physical activity. It is usually used to test aerobic endurance or cardiovascular fitness so that VO2 max can describe a person's functional capacity. Percentage of body fat can affect VO2 max. Based on data from the Sports Development Index (SDI) in Indonesia, 43.9% of young adults have a poor VO2 max. This study aims to determine whether or not there is a relationship between body fat percentage and functional capacity in young adults. Methods. The study used a cross-sectional method and was followed by 92 respondents throughout October and November 2022. Bioelectrical Impedance Analysis (BIA) is used to measure body fat percentage. The 6-minute Walk Test is used to measure VO2 max. Results. The results of the study showed that the bivariate analysis of the Fisher's Exact test obtained a significant relationship between body fat percentage (measured by BIA) and body functional capacity (VO2 max) (p=0.028). Conclusion. There was a significant relationship between body fat percentage through BIA measurements and functional capacity in young adults.